Pemahaman Moderasi Beragama dan Prilaku Intoleran terhadap Remaja di Kota-Kota Besar di Jawa Barat - Rabiah Al Adawiyah, Rabiah Al Adawiyah; Tobing, Clara Ignatia; Handayani, Otih (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2020)
Major cities in West Java like Bandung, Depok, and Bogor are often in the spotlight regarding the issue of tolerance for harmony among religious communities. In the Tolerant City Index issued by the Setara Institute in 2017 and 2018, although Bandung has moved from position 83 (2017) to 69 (2018), is yet unincluded in the top 50 tolerant cities. Meanwhile, Depok and Bogor moved from positions 90 and 92 (2017) to 88 and 89 (2018). Depok and Bogor are still in the top ten intolerant city in Indonesia. Therefore, further research is needed, especially on youth groups in these cities, since youth are the future generation of the nation. This study will describe the understanding and attitudes of youth in big cities in West Java in religion moderation and its correlation with intolerant behavior. This research was conducted using quantitative methods. First, the calculation of the population of senior high school students in 3 cities, namely Bandung, Bogor, and Depok was made. Then the population sample is determined using probability sampling. The data collection technique is done by giving questionnaires to respondents; the data obtained are tested for validity using the Pearson Product Moment correlation coefficient formula. The research results were obtained through multiple logistic regression analysis. The purpose of the results of this study was to determine the understanding and attitudes of senior high school students in religious moderation, the influence of religious education, and their correlation to student attitudes and interactions in inter-religious tolerance in 3 major cities in West Java.